Comic strip applications - Santos, Roberto Elísio dos (Comunicação & Educação, 2001)
Wrongly considered simply as uncommitted entertainment or sob-literature for children, the Comic Strip has qualities that its critics never even thought of. To use the comic strip in the learning process, for example, is a viable, necessary and important resource that has been poorly explored. Thus, this text aims at presenting the teaching and learning resources the comic strip has.